Wpisy Przemysława Czarnka na platformie "X" - wybrane aspekty = Przemysław Czarnek`s entries on the platform "X" - selected aspects - Hawrysz, Magdalena; Wojtysiak, Julia (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The sketch falls within the area of research on the media image of politicians. The study covered the examined entries on the platform "X" of one of the prominent politicians of the Law and Justice party, former Minister of Education and Science. The aim of the data collection is to identify the most characteristic stylistic properties of these messages and to analyze the politician`s entries in terms of the functions they perform, seen from the perspective of political communication.
Keywords: komunikacja polityczna; Czarnek, Przemysław (1977- ); platforma "X"; political communication; "X" platform